A Comparative Study of Muslim and Western Pedagoguesâ Educational Perspectives: Contextualization of Comparative Education as a Universitys Discipline - Arani, Abbas Madandar; Kakia, Lida; Moazani, Batol (EDUCARE, 2014)
ABSTRACT: During the two recent decades, the world has witnessed that regional conflicts are increasing because of the type of relationships among civilizations. Most of these conflicts have been resulted from political, social, and economical relations among Muslim countries and Western countries at the Middle East. In such a situation, for reducing millions of peopleâs sufferings, educational systems and especially higher education system surely play a vital role. Higher education system, through developing humanities-related disciplines, could increase levels of common understanding among intellectuals of the involved societies. On this score, comparative education has the power to encourage hearing other cultures out and international mutual understanding among people round the globe through educational system. Unfortunately, comparative education as a university discipline has not developed considerably at higher education systems in the Middle East countries. The present paper, first, tries to briefly explore the present situation of comparative education science in the region and, then, through comparing educational viewpoints of three Muslim pedagogues: Al-Farabi, Avicenna, and Al-Ghazali; and three famous educators of the West world: John Locke, Jean-Jacques Rousseau, and John Dewey, demonstrate the possibilities of developing comparative education science as a university discipline in the Middle East. The comparisons between Muslim educators and their counterparts in the West, however, made in this paper have bilateral benefits.KEY WORDS: Comparative education, educational perspective, Muslim, Middle East, pedagogues, Western, higher education system, and understanding.Â Â Â Â About the Authors: Dr. Abbas Madandar Arani is an Assistant Professor at the Department of Education LU (Lorestan University) in Iran; Mrs. Lida Kakia is a Ph.D. Student in Comparative Education at SU (Sofia University) in Bulgaria and at present works as a Teacher Counselor at different schools in Tehran, Iran; and Mrs. Batol Moazani is M.A. (Master of Arts) in Islam History and at present works as a Teacher at different schools in Tehran, Iran. The authors can be contacted via their e-mails at: rie2000@gmail.com and lida.kakia@gmail.comHow to cite this article? Arani, Abbas Madandar, Lida Kakia & Batol Moazani. (2014). âA Comparative Study of Muslim and Western Pedagoguesâ Educational Perspectives: Contextualization of Comparative Education as a Universitys Disciplineâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.111-118. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 29, 2013); Revised (January 20, 2014); and Published (February 17, 2014).Â Â